Entre as ruas e as mídias: das redes de hip hop aos circuitos de batalhas de rimas alagoanos - Barroso, Ibrahim Serra (2019)
This dissertation aimed to make a socio-anthropological study on the performance of young people engaged with hip hop in Alagoas. Thus, the research was developed in order to encompass the historical constitution of the first hip hop networks and circuits in the capital city, passing through the formation of possessions. And the new developments in which other forms of organizations such as collectives and studios emerge. The focus was on understanding how the actors constitute their group bonds and boundaries, as well as appropriating and resignifying the spaces and how they relate in the territories they occupy, in the exchanges, conflicts and negotiations that they establish in their networks and with the other spheres. of life in the ubran landscape. Through observations, conversations and in-depth interviews, I could understand how these young people mobilize resources to hold events. From this I mapped the plurality of meanings and subjectivities expressed in their narratives and performances. Finally, I present an ethnographic study of the rhyme battles that I followed between 2017 and 2019, in which I identify the roles and meanings produced in this framework of interactions.